Attitudes and Subjective Norms Regarding Medication for Opioid Use Disorder Among Individuals in Treatment for Opioid Use Disorder in the Greater St. Louis Area - Filiatreau, Lindsey M. (Journal of drug issues, 2025)
Medication for opioid use disorder (MOUD) is safe and efficacious for treating opioid use disorder (OUD), yet there is limited understanding of how attitudes and subjective norms regarding MOUD among individuals with OUD may impede treatment uptake. Thus, the current study describes attitudes and subjective norms in a sample of individuals with OUD in the St. Louis area (N = 183) and compares outcomes among those who were and were not actively taking MOUD. Most endorsed positive views regarding pharmacologic treatment for OUD overall, but concerns about physical side effects, the daily nature of some MOUD options, and uncertainty about the relative risks and benefits of MOUD remained prevalent. Individuals reporting current MOUD use had more accepting attitudes and perceived subjective norms regarding MOUD compared to others, suggesting that interventions targeting improvements in the knowledge of, attitudes toward, and normalization of MOUD are needed to further improve uptake and retention in pharmacotherapy for OUD.